Exploring Students’ Motivation in Learning English for Toefl Preparation at Industrial Engineering of Qomaruddin University - Elma Maghfiyah; Dina Amaliyah Mushthoza (Journal on Education, 2024)
Learning motivation is an encouragement that students received, either consciously or unconsciously, during the learning process to achieve their goals. This study focuses on student motivation in learning English for TOEFL preparation in the form of the Qomaruddin English Test (QET). The population and samples taken by researcher from second-semester students in the Industrial Engineering Study Program at Qomaruddin University, non English background. The researcher is interested in conducting research related to student motivation in learning English and factors that could affect student motivation in learning English for TOEFL preparation. The purpose of this study is to determine student motivation in learning English and to identify factors that can affect student motivation in learning English for TOEFL preparation. In this study, the researcher uses the descriptive- qualitative method. In collecting data, the researcher used questionnaires and interviews as instruments and analyzed the data through data reduction, data display, and conclusion drawing. The results of this study showes that students had two types of motivation, namely intrinsic motivation and extrinsic motivation. Factors that could affect student motivation were interest, learning environment, the role of lecturers, mood, and the demands of the world of work.